Metformin in the Management of Clomiphene Resistant Polycystic Ovarian Syndrome - Omole-Ohonsi, Abiodun; Nwokedi, Emmanuel (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5056 NJOG 2010 Jul-Aug; 5(1): 21-25